Effects of resveratrol on growth performance, immune function, and intestinal microbiota in Cherry Valley ducks - Gu, Tiantian; Wang, Yu; Chen, Yan; Li, Jian; Wang, Shiyu; Wang, Yonghai; Li, Xintong; Wang, Chunyang; Xiao, Fayi (Frontiers in Microbiology, 2025)
IntroductionThis study investigated the effects of stage-specific supplementation with 0.1% resveratrol on growth performance, immune function, and intestinal microbiota in Cherry Valley ducks from 1 to 42 days of age.MethodsA total of 300 1-day-old Cherry Valley ducks were randomly allocated into a control group (C) and four treatment groups (R1~R4). Resveratrol was administered via diet at 14, 21, 28, or 35 days of age until 42 days. Growth performance, slaughter traits, serum immune indices, and intestinal microbiota were analyzed.ResultsIn growth performance, the R1~R4 groups exhibited significantly improved slaughtering rates compared to the control (P < 0.01). The R1&R2 groups showed marked elevations in semi-evisceration rates (P < 0.001), while the R1 group displayed a significant increase in full-evisceration rate (P < 0.01). In terms of immune function, the R4 group demonstrated elevated serum IgA levels by 46.37%. All treatment groups exhibited upward trends in IgG. Complement C3 in the R2 group was markedly higher than the control (P < 0.0001). Interleukins IL-2 and IL4 were significantly upregulated in R1&R2 groups (P < 0.01). Thymus and spleen indices showed increasing trends in R3&R4 and R4 groups, respectively. With respect to intestinal microbiota, α-Diversity indices were significantly enhanced in R2&R4 groups (P < 0.001). β-Diversity analysis revealed distinct clustering between treated groups and controls. LEfSe analysis identified Bacteroides, Alistipes, and Faecalibacterium as biomarkers in R2&R4 groups, with pathogenic genera (Prevotellaceae, Desulfovibrio) reduced.DiscussionResveratrol supplementation improved slaughtering performance, immune competence, and intestinal homeostasis in Cherry Valley ducks. Resveratrol supplementation from day 21 (R2 group) showed the most favorable outcomes for growth-immunity-microbiota axis regulation, highlighting its potential as a precision nutrition strategy in waterfowl aquaculture.